Is a Responsive Business Also a Responsible Business? - Higgins , Colin (Journal of Law and Governance, 2010)
While much has been written about corporate responsibility, arguments for transformation in the business & society relationship prevail. In this paper, the dominant normative and business-case perspectives of corporate responsibility are examined in light of their assumptions regarding change. Both rely on modernist, firm-centred assumptions regarding management agency. Change in the business and society relationship may require closer attention being paid to processes of social norm formation.